Cloning and Sequencing Eukaryotic Small RNAs. Issue 8 (4th August 2022) - Crocker, Olivia J.; Trigg, Natalie A.; Conine, Colin C.
Abstract: Small RNAs are ubiquitous regulators of gene expression that participate in nearly all aspects of physiology in a wide range of organisms. There are many different classes of eukaryotic small RNAs that play regulatory roles at every level of gene expression, including transcription, RNA stability, and translation. While eukaryotic small RNAs display diverse functions across and within classes, they are generally grouped functionally based on the machinery required for their biogenesis, the effector proteins they associate with, and their molecular characteristics. The development of techniques to clone and sequence small RNAs has been critical for their identification, yet the ligation‐dependent addition of RNA adapters and the use of reverse transcriptase to generate cDNA in traditional library preparation protocols can be unsuitable to detect certain small RNA subtypes. In particular, 3′ or 5′ chemical modifications that are characteristic of specific types of small RNAs can impede the ligation‐dependent addition of RNA adapters, while internal RNA modifications can interfere with accurate reverse transcription. The inability to clone certain small RNA subtypes with traditional protocols results in an inaccurate assessment of small RNA abundance and diversity, where some RNAs appear over‐represented and others are not detected. This overview aims to guide users on how to design small RNA cloning workflows in eukaryotes to more accurately capture specific small RNAs of interest. Hence, we discuss the molecular biology underlying the identification and quantitation of small RNAs, explore the limitations of commonly used protocols, and detail the alternative approaches that can be used to enrich specific small RNA classes. © 2022 Wiley Periodicals LLC.